2013
DOI: 10.1111/trf.12500
|View full text |Cite
|
Sign up to set email alerts
|

Asking for something different from our donors: factors influencing persuasion success

Abstract: Converting suitable WB donors to plasmapheresis is best achieved early in the donor's career using face-to-face conversations with collection center staff. BCAs should facilitate donor-initiated conversations through promotional campaigns that encourage donors to approach staff. Conversations that focus on donors' needs and welfare more effectively encourage conversion intentions than those perceived as pushing the requirements of the BCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 42 publications
(85 reference statements)
4
40
1
Order By: Relevance
“…Each of these interventions mainly provided information about the plasma donation procedure and was successful in recruiting a significant number of new plasma donors. Nonetheless, it was recently shown that one-on-one conversation was the best approach to motivate whole blood donors to become plasma donors especially if the conversation was donor-oriented, that is, focusing on “donor's needs and welfare” [5]. This latter observation is in agreement with the results reported by Ferguson et al [6], showing that committed blood donors are more willing to donate blood when exposed to a benevolence message.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Each of these interventions mainly provided information about the plasma donation procedure and was successful in recruiting a significant number of new plasma donors. Nonetheless, it was recently shown that one-on-one conversation was the best approach to motivate whole blood donors to become plasma donors especially if the conversation was donor-oriented, that is, focusing on “donor's needs and welfare” [5]. This latter observation is in agreement with the results reported by Ferguson et al [6], showing that committed blood donors are more willing to donate blood when exposed to a benevolence message.…”
Section: Introductionsupporting
confidence: 79%
“…To our knowledge, in the scientific literature only a few studies have reported the impact of interventions on plasma donor recruitment [25]. Each of these interventions mainly provided information about the plasma donation procedure and was successful in recruiting a significant number of new plasma donors.…”
Section: Introductionmentioning
confidence: 99%
“…Bagot et al [30] identified key deterrents to conversion and provided preliminary strategies for agencies to recruit and retain to the plasmapheresis panel. These recruitment strategies were further clarified by Bagot et al [47] who identified that the key ingredients to successful ‘conversion conversations' are that they occur early in the donor's whole blood career, are donor-centric, and are, whenever possible, donor-initiated.…”
Section: Research Focus - Initiating and Maintaining Plasma Donationmentioning
confidence: 99%
“…Current research within this program is focused on identifying factors that promote flexible donor loyalty - that is retention in the context of being willing to move between panels [47]. This re-orientation away from the originally planned focus on plasma panel retention is in direct response to an emerging need to balance short- and long-term demand and supply [14] - challenge 2 .…”
Section: Research Focus - Initiating and Maintaining Plasma Donationmentioning
confidence: 99%
See 1 more Smart Citation